Kish as a small island towards sustainable tourism - Salim, Mona Erfanian; Mohd Tahir, Osman (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
Small islands are often encouraged to balance their economic and environmental concerns toward sustainable tourism. Universal experience shows that sustainable tourism in small islands should take into account their individual characteristics. This paper investigates the quality of sustainable tourism in a small island, namely, Kish in the South of Iran. Firstly, the main characteristics of small islands in relation to tourism sustainability are studied. Then the characteristics of Kish are identified as a small island. Finally, this study suggests that the crucial issue of sustainable tourism has been neglected in the development planning of the island. It is concluded with some recommendations for improving the development of Kish towards sustainable tourism. The results are generally applicable to other small islands. In addition, the results can be generalized to other tourist destinations in Iran or other countries with similar climatic and cultural conditions